Structural Changes of RNA in Complex with Proteins in the SRP - Flores, Janine K.; Ataide, Sandro F. (Frontiers in Molecular Biosciences, 2018)
The structural flexibility of RNA allows it to exist in several shapes and sizes. Thus, RNA is functionally diverse and is known to be involved in processes such as catalysis, ligand binding and most importantly, protein recognition. RNA can adopt different structures, which can often dictate its functionality. When RNA binds into protein to form a ribonucleoprotein complex (RNP), multiple interactions and conformational changes occurs with the RNA and protein. However, there is the question of whether there is a specific pattern for these changes to occur upon recognition. In particular when RNP complexity increases with the addition of multiple proteins/RNA, it becomes difficult to structurally characterise the overall changes using the current structural determination techniques. Hence, there is a need to use a combination of biochemical, structural and computational modelling to achieve a better understanding of the processes that RNPs are involved. Nevertheless, there are well-characterised systems that are evolutionarily conserved (such as the signal recognition particle (SRP)) that give us important information on the structural changes of RNA and protein upon complex formation.